Designing Nanosheet Heterostructures of CuO Grown on Bi2MoO6 as a Photoelectrochemical Biosensor for Detecting Alpha‐Fetoprotein. Issue 11 (1st June 2022) - Zhao, Mingxia; Yang, Liqin; Zhao, Jun; Jiang, Junbing; Wang, Zheng; Wang, Yuman; Cai, Zhenyu; Zhao, Zhiju
Abstract: Bi2 MoO6 (BM) was modified with various amounts of CuO. Photoelectrochemical (PEC) tests of the resulting CuO‐doped BM materials showed improved PEC performance. The best PEC performance was obtained for BM containing 5 wt % of CuO. CuO/BM‐5 % was then used as an active material for an Alpha‐fetoprotein (AFP) PEC biosensor. A PEC biosensor‐based CuO/BM‐5 % detected AFP linearly from 0.01–1200 ng ⋅ L −1 with a detection limit of 0.005 ng ⋅ L −1 . The photoelectron potential of the CuO/BM‐5 % heterojunction reduced the electron/hole recombination, which explains the excellent PEC performance of this material. Abstract : A semiconducting Bi2 MoO6 was doped with CuO and used as an active material to construct a biosensor based on a photoelectrochemical response. Under visible‐light irradiation, the photogenerated electrons on the conduction band (CB) of Bi2 MoO6 could migrate and recombine with the holes on the valence band (VB) of CuO. As a result, the holes on the VB of Bi2 MoO6 and the electrons on the CB of CuO are spatially separated.